Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/hep.31799
|View full text |Cite
|
Sign up to set email alerts
|

The Co‐mutational Spectrum Determines the Therapeutic Response in Murine FGFR2 Fusion‐Driven Cholangiocarcinoma

Abstract: Background and Aims Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver cancer and a highly lethal malignancy. Chemotherapeutic options are limited, but a considerable subset of patients harbors genetic lesions for which targeted agents exist. Fibroblast growth factor receptor 2 (FGFR2) fusions belong to the most frequent and therapeutically relevant alterations in ICC, and the first FGFR inhibitor was recently approved for the treatment of patients with progressed, fusion‐positive IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…A noteworthy finding is that 90% of patients diagnosed with ICC and having KRAS mutations also showed positive findings for FGFR 2 fusions, suggesting a potential collaborative role in promoting the progression of malignant tumors [ 65 ]. Consequently, it is hypothesized that the occurrence of FGFR 2 fusion in ICC might serve as an initial genetic occurrence that fosters the initiation and progression of tumorigenesis [ 66 ].…”
Section: Prevalence and Diversity Of Fgfr Abnormal...mentioning
confidence: 99%
“…A noteworthy finding is that 90% of patients diagnosed with ICC and having KRAS mutations also showed positive findings for FGFR 2 fusions, suggesting a potential collaborative role in promoting the progression of malignant tumors [ 65 ]. Consequently, it is hypothesized that the occurrence of FGFR 2 fusion in ICC might serve as an initial genetic occurrence that fosters the initiation and progression of tumorigenesis [ 66 ].…”
Section: Prevalence and Diversity Of Fgfr Abnormal...mentioning
confidence: 99%
“…A few studies have indicated that the use of genetically defined cellular and animal models can advance the discovery of actionable vulnerabilities associated with druggable iCCA oncogenic drivers. Specifically, three independent studies found that RAS-ERK signalling is necessary and sufficient to support the oncogenic activity of FGFR2 fusions in PDXs 91 , GEMMs 175 and organoid-based iCCA models 167 , and that combination therapies capable of more robust and durable suppression of RAS-ERK improve the therapeutic efficacy of clinically approved FGFR tyrosine kinase inhibitors 91,167,175 . Likewise, IDH1/KRAS-driven models have revealed that pharmacological targeting of mutated IDH1 sensitizes iCCA to host-mediated immune responses, which can be enhanced by concomitant administration of immune checkpoint inhibitors 121 .…”
Section: Addressing Clinical Needsmentioning
confidence: 99%
“…Gate keeper mutations can prevent the drug from accessing the hydrophobic pocket due to steric hindrance, and off-target resistance can impair longlasting response to FGFR inhibitors by acquiring new (epi-) genomic alterations that lead to activation of alternative signaling pathways [45]. In addition, the co-mutational status of the tumors is another relevant factor that may influence treatment response and has to be considered [46].…”
Section: Fgfr2 Alterationsmentioning
confidence: 99%